Effect of differences in vascular anatomy on surgical outcomes of left pancreatectomy: a retrospective study - Masahiro Fukada; Noriki Mitsui; Takeshi Horaguchi; Yuji Hatanaka; Itaru Yasufuku; Yuta Sato; Jesse Yu Tajima; Shigeru Kiyama; Yoshihiro Tanaka; Katsutoshi Murase; Nobuhisa Matsuhashi (World Journal of Surgical Oncology)
Abstract Background Minimally invasive left pancreatectomy (MILP) is increasingly performed worldwide, necessitating the need for improved understanding of vascular anatomy during surgery. However, the effect of differences in vascular anatomy on surgical outcomes remains unclear. In this study, we aimed to evaluate the effect of vascular anatomical variations on surgical outcomes and identify factors that influence open and minimally invasive surgery (MIS) outcomes. Methods This was a single-center retrospective study involving 123 patients who underwent left pancreatectomy (LP). We analyzed the correlation between vascular anatomical variations, namely, (i) the root of the splenic artery (SpA; types 1 and 2), (ii) the parent artery of the dorsal pancreatic artery, (iii) confluence patterns of the left gastric vein, and (iv) the inferior mesenteric vein, and surgical outcomes. We also performed a risk analysis of prolonged operation time, considering surgery-related factors. Results SpA type 2 was only significantly associated with longer operation time (p < 0.01) in LP procedures. In all LP cases, the pancreatic resection line (above the portal vein: odds ratio [OR] 3.47; 95% confidence interval [CI] 1.69–11.18; p < 0.01), the SpA type (type 2; OR 2.77; 95% CI 1.16–6.94; p = 0.02), and surgery type (MIS; OR 5.24; 95% CI 2.17–14.00; p < 0.001) were independently associated with prolonged operation times. In open-LP cases, high body mass index (> 24 kg/m2; OR 7.24; 95% CI 1.89–36.34; p < 0.01), tumor location (pancreatic body; OR 6.89; 95% CI 1.79–33.79; p < 0.01), and the SpA type (type 2; OR 5.86; 95% CI 1.72–24.65; p < 0.01) showed significant association with prolonged operations. In MILP cases, sex (male; OR 9.07; 95% CI 2.61–38.65; p < 0.001) and the pancreatic resection line (above the portal vein; OR 4.12; 95% CI 1.18–17.08; p = 0.03) showed significant associations. Conclusions SpA type 2 may negatively affect surgical outcomes. Therefore, it is important to recognize and approach vascular anatomy appropriately. MIS, especially robotic surgery, may be effective in mitigating the negative effects of variations in vascular anatomy.